Model Pembelajaran Project Based Learning Terhadap Kemampuan Pemecahan Masalah Matematika - Maya Nurfitriyanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
The purpose of this study was to determine effect of learning model project based learning to mathematic problem solving skills. This study was a quantitative research by eksperiment method. This study was doing in 2015 at one Senior High Schools in Bekasi Timur. Samples of this study were 70 students. Statistic test of this study using t test. The result of this study was there are effect of learning model project based learning to mathematic problem solving skills by t count was 3,87 and t table was 1,67. Keyword : mathematic problem solving skills, learning model project based learning.